An insight into the Clinical Profile, Treatment and Follow-up of Infections by a Rare Nosocomial Pathogen - “Elizabethkingia” species - Sweta Singh; Chinmoy Sahu; Sangram Singh Patel; Ujjala Ghoshal (Current Practice in Medical Science Vol. 10, 2022)
Background: Elizabethkingia species is an opportunistic nosocomially acquired Gram negative bacteria that has been linked to isolated cases of meningitis, pneumonia, bacteremia, and sepsis. Materials and Methods: The study included all clinical samples of blood, CSF, and respiratory specimens that tested positive for Elizabethkingia over a two-year period. The isolates were first identified by Vitek-2 GN card system and further confirmed by MALDI-TOF MS. Objective: The current study was planned to assess the 9 demographic profile, clinical picture, sensitivity patterns, species identification of various 10 Elizabethkingia isolates as well as follow up of the cases. Results: Over a period of two years, 27 cases showed positive growth of Elizabethkingia spp. Among these 27 patients, 19 were adults and 8 were neonates. Blood yielded maximum isolates 52.6% (n=10); followed by tracheal aspirate, bronchoalveolar lavage (BAL) fluid and cerebrospinal fluid (CSF). Drugs such as Minocycline and Piperacillin/Tazobactam showed 100% susceptibility in both the species of Elizabethkingia.Blood stream infections and meningitis were identified as the most common clinical conditions associated with mortality in positive patients. Conclusion: The cases and infections due to Elizabethkingia are on a rise in developing countries like, India.